Co‐infection of porcine epidemic diarrhoea virus and porcine deltacoronavirus enhances the disease severity in piglets. Issue 4 (22nd May 2021) - Zhang, Honglei; Han, Fangfang; Shu, Xiangli; Li, Qianqian; Ding, Qingwen; Hao, Chenlin; Yan, Xiaoguang; Xu, Menglong; Hu, Hui
Abstract: Porcine epidemic diarrhoea virus (PEDV) and porcine deltacoronavirus (PDCoV) are the main enteric coronaviruses that cause acute diarrhoea and dehydration in pigs. The co‐infection of PDCoV and PEDV is common in natural swine infections, but the clinical outcomes of the interaction between the co‐circulating PDCoV and PEDV are unknown. In current study, we established a co‐infection model by inoculating the cell culture‐adapted PDCoV HNZK‐02 strain and PEDV CV777 simultaneously or sequentially using 4‐day‐old piglets. The weight loss, clinical scores, viral load and titre, histopathological changes and serum cytokines expression were compared with piglets challenged by either virus. Our results indicated the piglets co‐inoculated with PDCoV and PEDV showed more serious diarrhoeal symptoms, mainly characterized by longer diarrhoeal period when compared to those of the mono‐infection piglets. Furthermore, we observed that PEDV could promote PDCoV replication in the co‐inoculated piglets with evidence of prolonged faecal viral shedding, high viral titres in faeces and intestine tissues. Histological analysis indicated the co‐infected piglets showed more extensive and serious pathological lesions in small intestine tissues than the mono‐infection piglets. Our data also suggested that the co‐infection of PDCoV and PEDV caused the excessive expression of pro‐inflammatory cytokines (IL‐6, IL‐8 and TNF‐α) in serum. These results proved there existed obvious synergistic pathogenic effects between PDCoV and PEDV co‐infection, which provided new insights into the synergistic pathogenic mechanism caused by these two porcine coronaviruses.